GENERASI ALPHA : TINGGAL DIANTARA - Raymond Arnold Manuel; Agustinus Sutanto (Jurusan Arsitektur dan Perencanaan, 2021)
The current Alpha generation is the youngest generation born in 2011 with an increasingly advanced technological approach, its familiarity with the world of technology is inseparable, but the Alpha generation classification does not materialize because there is no equitable distribution of education, facilities, and systems that are left behind. The urban village community experiences gaps so that some have to adapt to their abilities. This study uses an experimental material method using nails and magnets to create a unique spatial space. The resulting reaction becomes a metaphor for the movement of the Kampung Kota community in Jakarta which interacts with each other as a value for information exchange and the closeness that occurs. This is the basic concept of the experiment that has succeeded in making organic spaces for urban villagers, especially the Alpha generation who have adapted to the times.The experience that the author shares is a thought of planning for the future as an answer to